Electrocatalyst of RuO2 decorating TiO2 nanowire arrays for acidic oxygen evolution. (5th April 2023) - Liu, Yueren; Duan, Tigang; Xu, Likun; Gao, Xianze; Xue, Lili; Xin, Yonglei; Ma, Li; Huang, Guosheng; Liu, Tengteng
Abstract: Oxygen evolution reaction (OER) at the anode limits the efficiency of hydrogen production from water electrolysis substantially. A novel electrocatalyst of RuO2 decorating TiO2 nanowire arrays for OER was successfully prepared using a cyclic voltammetric method with electrodeposition of RuO2 nanoparticles on the TiO2 nanowire (TNW) arrays synthesized hydrothermally. Even though the electrodes with the composite electrocatalyst have a lower loading of RuO2, they have higher electrocatalytic activity and stability for acidic oxygen evolution than the Ti/RuO2 electrode prepared by conventional thermal decomposition method. The core-shell structure of the TNW@RuO2 electrocatalyst not only increases the specific surface area of the electrodes, but also inhibits the adverse effect of the poor conductivity of TiO2 . This novel OER electrocatalyst can improve the efficiency and reduce the cost of hydrogen production from electrolytic water splitting. Graphical abstract: Electrocatalyst of RuO2 -coating on TiO2 nanowire arrays display excellent activity and stability for acidic oxygen evolution. Image 1 Highlights: A novel electrocatalyst of RuO2 decorating TiO2 nanowire arrays was prepared. The loading of RuO2 is increased with the CV electrodeposition cycles. There exist rich oxygen vacancies on the surface of the TNW@RuO2 electrode. TNW@RuO2 electrode has large EASA and high OER electrocatalytic activity. Structures of TNW@RuO2 enhance the efficient utilization of RuO2 catalyst.